The common theoretical approaches to exploration of unreal modality in Slavonic languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper explores the meaningfulness of limitation of concept of modality with invariant meanings of reality / unreality, defines the contents of the term «unreality», determines the correlations of meanings – form – means as the necessary constituents of adequate description of modality in Slavonic languages.
Keywords: unreal modality; objective modality; reality / unreality; way to express the modality; the form to express the modality; the means to express the modality